Intra-hepatic cholestasis of pregnancy: A comprehensive review - Sangita Ghosh; Soumik Chaudhuri (Wolters Kluwer Medknow Publications, 2013)
Intra-hepatic cholestasis of pregnancy is a cholestatic disorder characterized by i) pruritus, with onset in the third trimester of pregnancy, without any primary skin lesions, ii) elevated fasting serum bile acids > 10 μmol / L (and elevated serum transaminases), iii) spontaneous relief of signs and symptoms within two to three weeks after delivery, and iv) absence of other disease that cause pruritus and jaundice. It is believed to be a multi-factorial disease with interplay between genetic, environmental and hormonal factors. Incidence is between 0.02% to 2.4% of all pregnancies; with wide geographical variations. Maternal prognosis is usually good but can result in adverse fetal outcomes like meconium staining of amniotic fluid, fetal bradycardia and even fetal loss. Response to anti-histaminic is poor. Of all the medical therapies that have been described for the treatment for IHCP, ursodeoxycholic acid has the best response in relieving pruritus in mother, and probably has a role in preventing even the perinatal complications. Timely diagnosis and treatment is urged in order to prevent fetal complications and an early delivery between 37 to 38 weeks should be contemplated in severe cases, especially once fetal lung maturity is attained.